Prediksi Kebangkrutan pada Bank BUMN dengan Menggunakan Metode Altman Z-Score Modifikasi Periode 2019 - Nita Kurniasih; Muhamad Umar Mai; Rani Putri Kusuma Dewi (Indonesian Journal of Economics and Management, 2020)
The purpose of this research is to predict the possibility of bankruptcy occur in company. The sample in this research used four state-owned banks, namely Bank BRI, Bank BNI, Bank Mandiri dan Bank BTN. The research method used is descriptive analysis techniques and tool used in predicting bankcruptcy is by using model Altman Z-Score modification. The research period used is the period 2019 with secondary data obtained from the annual financial report of state-owned bank. The result of this research conclude that all of four state-owned banks are in the grey area for the 2019 period because the value of the Z-Score obtained is between 1,10 and 2,90.